Notes on the genus Thunbergia (Acanthaceae) in Vietnam - Do, van Hai; Nguyen, Thu Thuy; Bui, Hong Quang; Duong, Thi Hoan; Choudhary, Ritesh Kumar; Deng, Yunfei (Phytotaxa, 2025)
This paper provides taxonomic notes on the genus Thunbergia in Vietnam. Thunbergia hossei is reported as a new record to the flora of Vietnam. In addition, a detailed description and photographs are provided of the insufficiently known T. eberhardtii. Lectotypes are designated for the names Thunbergia hossei and T. eberhardtii. A key to the Thunbergia species in Vietnam is provided.